Barriers and facilitators to implementing bubble CPAP to improve neonatal health in sub-Saharan Africa: a systematic review - Mai-Lei Woo Kinshella; Celia R. Walker; Tamanda Hiwa; Marianne Vidler; Alinane Linda Nyondo-Mipando; Queen Dube; David M. Goldfarb; Kondwani Kawaza (Frontiers Media S.A., 2020)
Abstract Background Bubble continuous positive airway pressure (CPAP) has been shown to be effective in supporting breathing in newborns with respiratory distress. The factors that influence implementation in resource-constrained settings remain unclear. The objective of this review is to evaluate the barriers and facilitators of CPAP implementation for newborn care at sub-Saharan African health facilities and how different facility levels and types of bubble CPAP systems may impact utilization. Methods A systematic search (database inception to July 2019) was performed on MEDLINE Ovid, EMBASE, CINAHL, The Cochrane Central Register of Controlled Trials (CENTRAL, The Cochrane Library), the WHO Regional Database for Africa, African Index Medicus (AIM), African Journals Online, grey literature and the references of relevant articles. Studies that met the inclusion criteria (primary research, bubble CPAP implementation with neonates ≤ 28 days old at a health facility in sub-Saharan Africa) were included in the review and assessed with National Heart, Lung, and Blood Institute of the National Institutes of Health (NIH) quality assessment tools. The review protocol was published to PROSPERO (CRD42018116082). Results Seventeen studies were included in the review. Reliable availability of equipment, effectively informing and engaging caregivers and staffing shortages were frequently mentioned barriers to the implementation of bubble CPAP. Understaffed neonatal units and high turnover of nurses and doctors compromised effective training. Provider-to-provider clinical mentorship models as well as affordability and cost-effectiveness of innovative bubble CPAP systems were identified as frequently mentioned facilitators of implementation. Conclusions With a strong recommendation by the World Health Organization for its use with premature infants with respiratory distress, it is important to understand the barriers and facilitators that can inform the implementation of bubble CPAP. More research is needed into health system factors that can support or impede the use of this potentially promising intervention.